Second Five Year Plan: A Draft Outline - Planning Commission, Government of India (Planning Commission, Government of India, 1956)
The beginning and the end of a five year plan are vital dates in the nation’s history. Each five year plan is both an assessment of the past and a call for the future. It seeks to translate into practical action the aspirations and ideals of the millions in the country and gives to each of us the opportunity of service in the common cause of eliminating poverty and raising standards of living.
Planning Commission Government of India
Planning Commission Government of India
Keywords: Second Five Year Plan- India